(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article focuses on the relevance of the professional development of personnel, the professional and pedagogical skills of teachers-historians, the essence and significance of socio-cultural competence. It also highlights topical issues of the development of socio-cultural competence of history teachers in the process of advanced training.